Can systemic inflammation markers obtained from complete blood count in the first trimester play a role in predicting early pregnancy loss? - Kanza Gül, Derya (Journal of Surgery and Medicine, 2020)
Aim: Ten percent of pregnancies result in early pregnancy loss, and in 40%, the cause is unknown. The purpose of this study is to evaluate the relationship between first trimester hematological inflammatory markers and early pregnancy loss. Methods: This retrospective case-control study was conducted at Department of Obstetrics and Gynecology at The Private Nisa Hospital between 1 January 2015 and 1 October 2020. A total of 611 patients were evaluated, including 310 patients with early pregnancy loss, and 301 patients, who were included in the study as the healthy control group. Sociodemographic data and complete blood count results of the groups were obtained by scanning hospital files and computer registration systems. Results: No statistically significant differences were detected between the two groups in terms of Red Cell Distribution Width (RDW), plateletcrit (PCT), Eosinophil and NLR (Neutrophil Lymphocyte Ratio) values (P>0.05 for all). In the early pregnancy loss group, PLT(P=0.004), MPV(P<0.001), PDW(P=0.005), PLR (platelet lymphocyte ratio) (P<0.001), ELR (eosinophil lymphocyte ratio) (P<0.001), and ENR (eosinophil neutrophil ratio) (P=0.004) values were higher, while WCB (P<0.001), Hemoglobin (P=0.007), Neutrophil (P<0.001), and Lymphocyte (P<0.001) values were lower, compared to the healthy control group. Conclusions: PLT, MPV, PDW, PLR, ELR and ENR were related with early pregnancy loss. Inflammation markers, thrombocyte activation markers and allergy markers obtained from Complete Blood Count (CBC) in the first trimester pregnancy constitute a cost-effective, and easy method to predict early pregnancy loss.